Performance of sustainable mortars containing blast furnace slag and fine concrete waste: an environmental perspective - Eric A. Ohemeng; Molusiwa S. Ramabodu; Tholang D. Nena; Yana Kancheva (Cogent Engineering, 2024)
AbstractAbout 9% of the globe’s carbon dioxide (CO2) emissions are attributed to cement production. The replacement of cement with blast furnace slag and fine concrete waste (FCW) could reduce the CO2 emissions associated with the construction sector. Consequently, the main objective of the current study is to examine the combined effect of blast furnace slag and FCW on mortar manufacturing. The experimental study was conducted in three stages. In stage I, mortars were prepared using cement-to-sand ratio of 1:3. The cement was substituted with FCW at 0.00, 0.30, 0.60 and 0.75 fractions. From the Stage I results, a mortar mixture prepared with 60% FCW and 40% cement was chosen for the Stage II study. In place of cement, slag was used in fractions of 0.00, 0.05, 0.10, 0.15, 0.20 and 0.25. The strengths of the mortars were significantly enhanced when slag was employed as a replacement for cement. In the final stage of the study, the environmental impact (EI) of producing FCW was evaluated. The results show that the EI values for producing FCW are far below those of cement and slag. For instance, the global warming potentials of producing cement, slag, and FCW were 0.951 kgCO2eq, 0.0188 kgCO2eq and 0.0169 kgCO2eq, respectively. In conclusion, the produced mortars provided the specified strength requirements for masonry works as well as environmental and economic benefits, making them sustainable.